PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 009 TANJUNG LEBAN KECAMATAN KUBU KABUPATENROKAN HILIR - Hamdani Hamdani; Eddy Noviana; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Absract: This research carried out based on the lowly of the social studies student adhievment with an average grade 56,75. While the minimum criteria of completeness is 65. This research is classroom action research (CAR). Which aims to increase the social students achievment at fourth grade of V on SDN 009 Tanjung Leban Kecamatan Kubu, Kabupaten Rokan Hilir. The formulation of the problem : Does the application of Examples Non Examples can increase the social students achievment at fourth grade of elementari school 009 Tanjung Leban Kecamatan Kubu Rokan Hilir District. The resulth of studen achievmen before CAR with average 56,75% in fair category, whereas after CAR in cycle 1 with average 67,5% in fairly good category and in cycle 2 with average 72% in excellen categiri. From the data can see the comparison between increasing the students achievmen from the based secore to cycle 1 is about 18,94%. Whereas from the based score to cycle 2 about 26,87%. The average of teacher,s aktivity in first cycle about 58,33% whereas in scond cycle about 79,16% and the students activity infirst cycle about 54,16 andthe scord cycle about 75%. The result of this research is the application of cooperative learning model type Examples Non Examples can increase the social studies students learning outcomes at fourth brade of elementary school 009 Tanjung Leban Kecamatan Kubu, Kabupaten Rokan Hilir.Keywords : examples non examples, social studies learning outcome